Measurement of triple-gauge-boson couplings of the W boson at LEP - Dova, María Teresa (2004)
The CP-conserving triple-gauge-boson couplings, gZ1 , κγ , λγ , gZ5 , κZ and λZ are measured using hadronic and semi-leptonic W-pair events selected in 629 pb−1 of data collected at LEP with the L3 detector at centre-of-mass energies between 189 and 209 GeV. The results are combined with previous L3 measurements based on data collected at lower centre-of-mass energies and with the results from single-W production and from events with a single-photon and missing energy. Imposing the constraints κZ = gZ1− tan2 θW(κγ − 1) and λZ =λγ , we obtain for the C and P conserving couplings the results: gZ1= 0.966 ± 0.033(stat) ± 0.015(syst), κγ =1.013 ± 0.066(stat) ± 0.026(syst), λγ =−0.021 ± 0.035(stat) ± 0.017(syst). Results from the analysis of fully leptonic W-pair decays are also given. All results are in agreement with the Standard Model expectations and confirm the existence of self-couplings among electroweak gauge bosons.